Multidimensional Project Portfolio Management in The Context of The Current Covid-19 Situation in The Automotive Industry: A Case Study - Agnieszka JĘDRUSIK (Communications of International Proceedings, 2022)
In recent times, the economic situation has changed significantly. The ubiquitous pandemic has caused numerous problems not only with human resources, but also with access to components necessary to produce the final product for the customer. Managing projects or portfolios of projects in the automotive industry in connection with the current situation is a challenge not only for the project management team but also for all departments and individuals involved in its implementation. Therefore, due to the complexity of the product, the diversity of the supplier market and the diversification of customers there is a need to develop a matrix that will allow efficient and effective management of the project portfolio from the concept phase to the final implementation at the customer. In order to do that an in-depth analysis of all customers contributing to BorgWarner Poland's profit, analysis of internal and external requirements as well as an overview of the process for achieving milestones is necessary. The Covid 19 situation made it necessary to develop a schema/matrix that could be a universal tool that could be implemented for any group of projects or programs in the organization. Therefore, the purpose of this article is to develop such a matrix that will allow to assess whether the project is carried out from the initiation phase to the completion phase in accordance with norms and internal standards as well as customer requirements and whether the appropriate allocation of resources took place. This matrix is intended to be a universal tool that can be implemented in other industries as well.